Evidence-based vs. social media based high-intensity interval training protocols: Physiological and perceptual responses. - Katie L Hesketh (Public Library of Science (PLoS), 2021)
Objective High intensity interval training (HIIT) is a time-efficient exercise modality to improve cardiorespiratory fitness, and has recently been popularised by social media influencers. However, little is known regarding acute physiological and perceptual responses to these online protocols compared to HIIT protocols used within research. The aim was to investigate acute physiological, perceptual and motivational responses to two HIIT protocols popular on social media, and compare these to two evidence-based protocols. Methods Twenty-seven recreationally active (>1 exercise session /week) participants (Age: 22±3y, BMI: 24.3±2.4) completed a randomised cross-over study, whereby each participant completed four HIIT protocols, two already established in research (Ergo-60:60 (cycling 10x60s at 100%Wmaxwith 60s rest), BW-60:60 (body-weight exercises 10x60swith 60s rest)) and two promoted on social media (SM-20:10 (body-weight exercises 20x20swith 10s rest) and SM-40:20 (body-weight exercises 15x40s with 20s rest)). Blood lactate, heart rate (HR), feeling scale (FS), felt arousal scale (FSA), enjoyment and perceived competence were measured in response to each protocol. Results Significant differences were observed between BW-60:60 and SM-20:10 for the proportion of intervals meeting the ACSM high-intensity exercise criterion (>80% of HRmax) (BW-60:60 93±10%, SM-20:10 74±20%, P = 0.039) and change in lactate (BW-60:60 +7.8±3.7mmol/L, SM-20:10 +5.5±2.6mmol/L, P = 0.001). The percentage of time spent above the criterion HR was also significantly lower in SM-20:10 compared to all other protocols (Ergo-60:60 13.9±4.9min, BW-60:60 13.5±3.5min, SM-40:20 12.1±2.4min, SM-20:10 7.7±3.1, P<0.05). No differences were observed in lowest reported FS between protocols (P = 0.268), but FS decreased linearly throughout Ergo-60:60 and BW-60:60 (first vs. last interval P<0.05), but not in SM-20:10 or SM-40:20 (P>0.05). Enjoyment was higher upon completion of BW-60:60 compared to Ergo-60:60 and SM-40:20 (P<0.05). Conclusions This study shows that HIIT protocols available on social media offer an interesting real-world alternative for promoting exercise participation. Future studies should continue to investigate these highly popular and practical HIIT protocols.